O fomento da criatividade em práticas de cozinha no ensino superior utilizando PANC - FERREIRA, Bruno de Souza (Universidade Federal do Pará, 2023)
Research presented in this master's dissertation focuses on creating, applying, and analyzing an external learning trail for students of the Gastronomy course to promote creativity in cooking practices using Non-Conventional Food Plants (PANC). In this case, red nettle (Laportea estuans) was the PANC under study. As part of this research, we are asking: How can non-conventional food plants be used to foster Creativity among students of higher education? This questioning led to the following general objective: Design an educational process to foster Creativity competence in kitchen practices in the training of Gastronomy course students, with non-conventional food plants (PANC) as content. Action research methodology, considering its connection to qualitative research approaches, seeks to promote changes in the reality context, but also educate and raise awareness of participants and the researcher. Learning is divided into four dimensions related to cooking: knowing, cooking, eating, and convincing. Activity activities subsidized by educational artists (podcast and illustrated booklet) are used for the learning trail, along with support materials (map mind, sensory evaluation form, technical sheet), that each moment of the trail helps to develop specific creative skills. This study was conducted with students in the 3rd semester of the Higher Course of Technology in Gastronomy at the Universidade da Amazônia (Unama) in 2022 within the scope of the discipline "Integrating Topics II". Students were assessed based on their previous knowledge of the PANC under study. An analysis of the student's creative process was carried out in the form of interviews to analyze their innovative and creative recipes made from red nettle. The research data shows that the learning trail contributed to the objectives it proposed, such as promoting creativity in students' activities and promoting the gastronomic exhibition.